Atenolol characterization in solid formulations available in Brazilian market - Salvi, S. T. B.; Antonio, S. G.; Santos, Carlos de Oliveira Paiva [UNESP] (Cambridge University Press (CUP), 2013)
Atenolol is the most used drug in Brazil to hypertension treatment. Two crystal structures are known for this molecule: a racemic form (R,S)-atenolol and a pure form S-atenolol. The racemic form is found in commercial tablets. X-ray powder diffraction (XRD) is an adequate tool to study crystalline structures including drugs. Using the Rietveld Method with XRD data it is possible to quantify the crystalline structures existing in the raw material. Other methods like Le Bail and Pawley can be used to the profile fit and phases identification. For this work we analyzed three tablets of atenolol, two generics and the reference (materials were purchased from a drugstore at the city of Araraquara). These tablets were analyzed by Rietveld, Le Bail and Pawley methods. All tablets exhibited the racemic mixture API (R,S)-atenolol. Some crystalline excipients could be characterized: magnesium carbonate hydrate, lactose monohydrate and talc. The conclusion is that the three methods can be efficiently used to characterize the three atenolol tablets.
Keywords: Atenolol; Rietveld method; Le Bail method; Pawley method; Pharmaceutical; X-ray powder diffraction